2021
DOI: 10.4049/jimmunol.2001053
|View full text |Cite
|
Sign up to set email alerts
|

Itk Promotes the Integration of TCR and CD28 Costimulation through Its Direct Substrates SLP-76 and Gads

Abstract: The costimulatory receptor CD28 synergizes with the TCR to promote IL-2 production, cell survival, and proliferation; yet the obligatory interdependence of TCR and CD28 signaling is not well understood. Upon TCR stimulation, Gads, a Grb2-family adaptor, bridges the interaction of two additional adaptors, LAT and SLP-76, to form a TCR-induced effector signaling complex. SLP-76 binds the Tec-family tyrosine kinase, Itk, which phosphorylates SLP-76 Y173 and PLC-γ1 Y783. In this study, we identified TCR-inducible,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…The appearance of ADAP Y571 was particularly interesting as it promotes both ADAP/STAT3 interaction and subsequent STAT3 phosphorylation, the latter of which was also observed in the form of STAT3 T716S727 by TiO 2 enrichment (Figure A). Crucially, sSH2 enrichment indicated increased phosphorylation of GADS Y45 (Figure A), an Itk substrate site that is phosphorylated exclusively within the LAT-SLP76 complex . The primary function of SLP76 complex is to activate critical signaling pathways downstream of the TCR, including p38/Jnk, MAPK/Erk1/2 and subsequent pathways regulating the actin cytoskeleton. , The guanine exchange factor, Vav1, is a component of the SLP76 complex known to activate Rho/Rac GTPases after TCR stimulation. , sSH2 pTyr enrichment revealed that Vav1 Y791 , a pTyr site known to increase in response to α-CD3 and α-CD28 treatment, significantly increased upon CAR activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of ADAP Y571 was particularly interesting as it promotes both ADAP/STAT3 interaction and subsequent STAT3 phosphorylation, the latter of which was also observed in the form of STAT3 T716S727 by TiO 2 enrichment (Figure A). Crucially, sSH2 enrichment indicated increased phosphorylation of GADS Y45 (Figure A), an Itk substrate site that is phosphorylated exclusively within the LAT-SLP76 complex . The primary function of SLP76 complex is to activate critical signaling pathways downstream of the TCR, including p38/Jnk, MAPK/Erk1/2 and subsequent pathways regulating the actin cytoskeleton. , The guanine exchange factor, Vav1, is a component of the SLP76 complex known to activate Rho/Rac GTPases after TCR stimulation. , sSH2 pTyr enrichment revealed that Vav1 Y791 , a pTyr site known to increase in response to α-CD3 and α-CD28 treatment, significantly increased upon CAR activation.…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, sSH2 enrichment indicated increased phosphorylation of GADS Y45 (Figure 5A), an Itk substrate site that is phosphorylated exclusively within the LAT-SLP76 complex. 76 The primary function of SLP76 complex is to activate critical signaling pathways downstream of the TCR, including p38/Jnk, MAPK/Erk1/2 and subsequent pathways regulating the actin cytoskeleton. 15,77 The guanine exchange factor, Vav1, is a component of the SLP76 complex known to activate Rho/Rac GTPases after TCR stimulation.…”
Section: Signaling From the Lat-slp76 Complexmentioning
confidence: 99%
“…It will also be important to map the CD28-downstream signaling pathway to understand both the increase and subsequent decrease in TCR translation that occur during the translation burst. We found that AKT influences the rapid rise in translation ( Figure 4E–F ), but other kinases such as Tec-kinases ( Andreotti et al, 2018 ; Gallagher et al, 2021 ; Hallumi et al, 2021 ) could also impact the translation burst.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies also indicated that proper T cell activation requires cooperative interactions between several members of the LAT-SLP76 signalosomes leading to the formation of large multiprotein complexes (9)(10)(11)(12). For example, multipoint binding facilitates recruitment to the LAT-SLP76 complex of the ITK and PLCg1 effectors which are involved in calcium release (13)(14)(15)(16). TCR signal diversification is also enhanced by the phosphorylation of transmembrane molecules which provide additional docking sites for adaptors localized near the priming module.…”
Section: Introductionmentioning
confidence: 99%